Implementasi Kebijakan Low Emission Zone (LEZ) melalui Forum C40 Cities di Provinsi DKI Jakarta (2021-2023) - Syalom, Yusuf Edwin; Astuti, Wiwiek Rukmi Dwi (Kementerian Luar Negeri Republik Indonesia, 2024)
In response to the issue of air quality in DKI Jakarta, characterized by high levels of air pollution, the Jakarta Provincial Government, in collaboration with Cities 40, has introduced a new environmental policy called the Low Emission Zone (LEZ). This policy is implemented in the Kota Tua area and Tebet Eco Park. This research aims to explain the implementation process of the LEZ and the connection between the Jakarta Provincial Government's paradiplomacy efforts and C40 The study utilizes qualitative descriptive methods, including interviews and literature review, for data collection The findings reveal cooperation between the Jakarta Provincial Government and Cities 40, encompassing technical assistance, financial support, and technology aid. However, the implementation of the Low Emission Zone (LEZ) is actually an initial step that is still limited, thus requiring a more comprehensive strategy to achieve the targeted results.